Pulsation-assisted fluidised bed drying of heat-sensitive and sticky materials: effect of basic parameter, and pulsation-specific parameter - Luqman, Abdul Halim; Firdaus, Basrawi; Ahmmad Shukrie, Md Yudin; Nurul Aini, Mohd Azman; Oumer, Ahmed Nurye; Shamsul Bahri, Abd Razak (Taylor & Francis, 2022)
Fluidized bed dryer (FBD) is an excellent drying method due to its high degree of mass and heat transfer rate. Generally, increasing the temperature in the range of 30 and up to 140 °C can significantly improve the drying rate. However, for heat-sensitive materials, excessive heat can diminish their quality and nutrients. For example, up to 57% of rice is damaged due to drying in FBD at 80 °C. Due to higher moisture content, some materials become sticky and may form agglomerates. Hence, this article reviews basic drying, drying models, and state of the art of FBD drying, its modification and agglomerates breaking without heating by pulsation-assisted fluidized bed dryer (PFBD). Improving the drying rate will involve treatment process to the bed material, such as pretreatment, tempering, and addition of inert particles; or modification of the fluidized bed dryer itself; adding dielectric heating, swirling nozzle distributor, and pulsed flow. PFBD has been reported to improve drying rate especially for sticky and difficult- to-fluidize particles. Thus, for heat-sensitive sticky materials, drying performance can be improved further through combinations of various FBD modifications with minimal effect toward its quality.